2018
DOI: 10.1080/23322039.2018.1534528
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related crime and poverty in South Africa

Abstract: This paper argues that the link between poverty and drug-related crime might be spurious. We take an empirical approach to investigate the causality and plausibility of this link. Firstly, we regress crime against envisaged explanatory variables in order to estimate the contribution of poverty to crime. Secondly, data is analysed using an ARDL ECM. The quarterly sample data for our estimation is for the period 1995-2016. We found a strong association between crime and poverty both in the short and long run. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 51 publications
0
20
0
1
Order By: Relevance
“…The importance of socio-economic contexts in relation to drug use has been studied, highlighting poor living conditions, limited access to education and employment, poor neighborhoods and housing characteristics which may influence drug-related behaviors [1][2][3][4][5]. In 2016, an estimated 25 million children (26.4%) living in the European Union (EU) Member States were at risk of poverty [6].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of socio-economic contexts in relation to drug use has been studied, highlighting poor living conditions, limited access to education and employment, poor neighborhoods and housing characteristics which may influence drug-related behaviors [1][2][3][4][5]. In 2016, an estimated 25 million children (26.4%) living in the European Union (EU) Member States were at risk of poverty [6].…”
Section: Introductionmentioning
confidence: 99%
“…South Africa is regarded by many as the crime capital of the world and the socio-political landscape being characterized by high rates of poverty, socioeconomic inequality, and high crime rate [ 29 ] - three social evils. [ 30 ] Apart from these three key social challenges, a large body of research suggests that African women face serious socioeconomic marginalization and domestic violence that can hamper their empowerment potential [ 31 ] and diminish their confidence [ 32 ] and sense of dignity, [ 33 ] which in turn can prevent them from adopting healthy lifestyle behavior such as regular PE. [ 34 , 35 ] A USA based study (metropolitan Boston) including urban low-income housing complexes reported that residing in a neighborhood perceived to be unsafe at night was a barrier to regular PE especially among women, living in low-income housing.…”
Section: Discussionmentioning
confidence: 99%
“…(Fraser et al ., 1996; Crookes and Lyne, 2001; Makhura and Wasike, 2003; Finnemore et al ., 2004; Chaminuka et al ., 2008; Cheteni, 2013; Makhura, 2016; Kunzekweguta et al ., 2017; Cheteni et al ., 2018; Chaminuka et al ., 2019)…”
Section: Data Analysis and Interpretationmentioning
confidence: 99%
“…Bibliometric involves the two‐way process that comprises of performance evaluation and discipline representation. The former evaluates data in terms of authors, countries, subjects and funding agencies) (Uddin et al ., 2013; Dunne and Tian, 2015; Sulaiman and Aluko, 2015; Meyer et al ., 2017a, 2017b; Meyer and McCamel, 2017); whereas the latter targets the fundamental and strong aspects of research in the form of different layouts (pictorial representation) (Makhura, 2016; Kunzekweguta et al ., 2017; Cheteni et al ., 2018; Deléchat et al ., 2018). Broadly, it provides a rational investigation of the research theme in hand.…”
Section: Introductionmentioning
confidence: 99%